MODERASI DEFERRED TAX EXPENSE ATAS RELEVANSI NILAI LABA DAN BUKU EKUITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2008-2010 - Ni Putu Eka Widiastuti; Carmel Meiden (Universitas Trunojoyo Madura, 2012)
Accounting research has taken a keen interest in the relation between companies’ share price and the two summary accounting measures, namely earning and equity book value. In this study, we use deferred tax expense as moderating variable to explore the correlation between stock price, earning and equity book value.The purpose of this study is to determine the level of influence earning information and equity book value to share price and to know whether the deferred tax expense (DTE) which is a moderating variable to strengthen or weaken the relationship between earning information and equity book value to the price of shares in companies listed in Indonesia Stock Exchange. The population in this study is manufacturing companies listed in Indonesia Stock Exchange 134 companies in 2008-2010. The results of this study indicate that the variable earning information has positive correlation on stock prices. Meanwhile, there is negative correlation between equity book value and stock prices. Further research also showed that DTE as a moderating variable weaken the relationships between earning information and equity book value and the stock price.